“LSP teaching – current trends, desiderata, research perspectives”. Institute of Applied Linguistics of Adam Mickiewicz University, Poznań, Poland, 05-06.07.2023 - Ammari, Maria (Glottodidactica, 2024)
The “LSP Teaching – Current Research Trends, Desiderata, Research Perspectives” conference was held in Poznan on July 5-6, 2023. The venue of the conference’s was the Collegium Novum, and it was organized by the institute of Applied Linguistics UAM and the LSP Teacher Education Online Course for Professional Development Consortium. The conference included many renowned participants and was distinguished by its intimate and supportive atmosphere, fostering a collaborative spirit that resonated with both academics and practitioners in the field of Languages for Specific Purposes (LSP).